BASIC IMPLEMENTATION OF THE NATIONAL OFFICE IN PREVENTION OF GRATUITY CASES - Ahmad Taqwa; Muhammad Ihsan (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The scientific background regarding the case of gratuity in Indonesia, in terms of juridical violations under Articles 12A, 12B, and 12C of Law Number 31 of 1999, in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption Crimes, has caused poverty across various aspects of people’s lives. In addition, efforts to eradicate the crime of gratuity need to be supported by professional human resources and the enforcement of legal sanctions to foster personal awareness of anti-corruption. Based on the description above, the problem formulation is focused on: 1) Why is the integrity of state officials needed in eradicating graft cases? 2) What is the relationship between the philosophical study of the integrity of state officials in the case of gratuities? 3) What is the legal purpose of the integrity of state officials in the case of gratuities? The purpose of this study is to analyze the integrity of state officials in eradicating cases of gratuity. The approach method in this study is a normative juridical approach. The types of legal materials used are primary, secondary, and tertiary. The analysis technique used is qualitative descriptive. The results of the study are the eradication of gratuities in Indonesia, namely unlawful acts (corruption) by state officials/employees, receiving bribes (gratuities) from corporations or related parties, abuse of authority, and the practice of collusion with fictitious projects offering a 50%:50% profit split with contractors. This research novelty concludes that gratuities are unlawful acts by state officials who must be audited their salary financial data and even their family’s financial data through the Annual Personal Tax Payment Letter in accordance with the Regulation in Lieu of Law Number 1 of 2017 and reported to the Financial Audit Agency and the Financial Transaction Analysis Reporting Center in accordance with the Law of the Republic of Indonesia Number 8 of 2010.